Pancakes, pancakes! - Carle, Eric. (New York : Little Simon, 2004)
By cutting and grinding the wheat for flour, Jack starts from scratch to help make his breakfast pancake.
On board pages.
Keywords: Pancakes, waffles, etc. -- Juvenile fiction; Cooking -- Juvenile fiction; Board books; Picture books